2017
DOI: 10.1002/slct.201702370
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Thioketals into Methylene and Methyl Derivatives: Nickel or not Nickel?

Abstract: In this review, the desulfurization of thioacetals and thioketals leading to methyl and methylene derivatives is summarized through metal and metal-free methodologies. In the section concerning the use of metals for desulfurization reactions, we will be successively presenting and discussing all methods requiring Ni and Ni derivatives as reducing agents and other examples in which metals were used to generate solvating electrons as reducing species. The following section will concern the use of other desulfuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…desulfurized at r.t. [17] in CH 2 Cl 2 using this metal-free process in a Mozingo-type reaction. [18] By replacing CH 2 Cl 2 by CH 3 CN as the reaction solvent, we surprisingly observed that dithianes derivatives were not reduced into methylene substrates but were totally and cleanly deprotected into ketones. It seemed interesting to study this method for the deprotection of thioacetals which does not use metal salts, oxidants, toxic or expensive reagents ( Figure 1).…”
Section: Introductionmentioning
confidence: 92%
“…desulfurized at r.t. [17] in CH 2 Cl 2 using this metal-free process in a Mozingo-type reaction. [18] By replacing CH 2 Cl 2 by CH 3 CN as the reaction solvent, we surprisingly observed that dithianes derivatives were not reduced into methylene substrates but were totally and cleanly deprotected into ketones. It seemed interesting to study this method for the deprotection of thioacetals which does not use metal salts, oxidants, toxic or expensive reagents ( Figure 1).…”
Section: Introductionmentioning
confidence: 92%
“…Further elaborations, includingr emoval of the sulfones and inversion of the lactones tereocenter,a fforded epimeric constanolactones 98 and 99. [40] Ab is(sulfone) also figuredp rominently into Takahashi's synthesis of dimethylg loiosiphone A ( 104). Sequential Pd-catalyzed allylic alkylationso fB PSM 4 with allylic acetate 100 and allylic bromide 101 furnished triene 102,w hich was transformed intos pirocycle 103 by aP d-catalyzed cycloisomerization reaction (Scheme23).…”
Section: Secondary Carbon Synthonsmentioning
confidence: 99%
“…Sequential Pd-catalyzed allylic alkylationso fB PSM 4 with allylic acetate 100 and allylic bromide 101 furnished triene 102,w hich was transformed intos pirocycle 103 by aP d-catalyzed cycloisomerization reaction (Scheme23). After reductive cleavageo ft he sulfonyl groups, further elaboration of the core carbon skeleton in 103 eventually gave rise to dimethyl gloiosiphoneA (104). [41] Bis(sulfones)c an also be used to disconnect complexm olecules in the middle of an alkyl chain.…”
Section: Secondary Carbon Synthonsmentioning
confidence: 99%
See 2 more Smart Citations